Kawasan Tanpa Rokok Di Angkutan Umum - Saleha Fatma Lubis; Syafri Gunawan; Khoiruddin Manahan Siregar (Jurnal El-Thawalib, 2021)
This thesis discusses the implementation of Law No. 36 of 2009 Article 115 paragraph 1 letter E concerning a smoke-free area on public transportation in Panyabungan District, Mandailing Natal Regency. This research is motivated by the existence of problems that often occur and are found in the Panyabungan sub-district, Mandailing Natal district, namely the habit of smoking in public transportation facilities as well as in village transportation carried out by the community, both the community as a public transport driver and the community as a passenger so that the habit What the community does is clearly violates law number 36 of 2009 precisely in article 115 paragraph 1 letter E which in that article prohibits smoking in non-smoking areas, namely on public transportation. The type of research used by the researcher is descriptive qualitative research. The data used are primary and secondary data. Data collection methods include observation, interviews, and documentation. The data collected were analyzed using editing, verification, and analysis methods. In this study the researchers found the results that the implementation of a smoke-free area in village transportation in the Panyabungan sub-district, Mandailing Natal district, had been implemented but it was still far from the maximum, this was due to the inhibiting factors of its implementation such as: lack of socialization carried out by the government with the community, lack of information and knowledge of the community, its human resources, the narrowness of people's thinking both as passengers and transport drivers, the absence of a special team, the absence of a budget, the absence of supervision, and the lack of support from the local government.